Novel copper(II) phthalocyanines as semiconductor layer in organic field effect transistors: Synthesis and investigation of electrical properties - Demir, Sevde; Akbay, Semih; Canimkurbey, Betul; Yüksel, Fatma (Elsevier, 2024)
New two tetra-peripheral/non-peripheral substituted copper(II)-phthalocyanines have been synthesized and characterized by using ATR-IR, MALDI-TOF/MS and UV-Vis spectroscopy. The electrical characterization and conducting properties of copper(II)-phthalocyanine compounds have been achieved in order to determine their use as a semiconductor layer in organic field effect transistors (OFETs). The OFETs characterization has been performed and the tetra-peripheral/non-peripheral substituted copper(II)-phthalocyanines OFET carrier mobility of about 1.31x10(-3) cm(2)/V.s and 1.42x10(-3) cm(2)/V.s, respectively. On/off current ratio of similar to 10(3) and similar to 10(2); threshold voltage of (-30 V, -32 V), respectively were measured.
Keywords: Copper(II)phthalocyanine; Pentaerythritol hub; OFET; Mobility